Two Words, One Meaning: Evidence of Automatic Co-Activation of Translation Equivalents - Dimitropoulou, Maria; Duñabeitia, Jon Andoni; Carreiras, Manuel (Frontiers in Psychology, 2011)
Research on the processing of translations offers important insights on how bilinguals negotiate the representation of words from two languages in one mind and one brain. Evidence so far has shown that translation equivalents effectively activate each other as well as their shared concept even when translations lack of any formal overlap (i.e., non-cognates) and even when one of them is presented subliminally, namely under masked priming conditions. In the lexical decision studies testing masked translation priming effects with unbalanced bilinguals a remarkably stable pattern emerges: larger effects in the dominant (L1) to the non-dominant (L2) translation direction, than vice versa. Interestingly, this asymmetry vanishes when simultaneous and balanced bilinguals are tested, suggesting that the linguistic profile of the bilinguals could be determining the pattern of cross-language lexico-semantic activation across the L2 learning trajectory. The present study aims to detect whether L2 proficiency is the critical variable rendering the otherwise asymmetric cross-language activation of translations obtained in the lexical decision task into symmetric. Non-cognate masked translation priming effects were examined with three groups of Greek (L1)-English (L2) unbalanced bilinguals, differing exclusively at their level of L2 proficiency. Although increased L2 proficiency led to improved overall L2 performance, masked translation priming effects were virtually identical across the three groups, yielding in all cases significant but asymmetric effects (i.e., larger effects in the L1→L2 than in the L2→L1 translation direction). These findings show that proficiency does not modulate masked translation priming effects at intermediate levels, and that a native-like level of L2 proficiency is needed for symmetric effects to emerge. They furthermore, pose important constraints on the operation of the mechanisms underlying the development of cross-language lexico-semantic links.